Teachers as Learners: The Impact of Teachers' Morphological Awareness on Vocabulary Instruction - Joanna Newton (MDPI AG, 2018)
Academic vocabulary knowledge is central to reading and academic achievement. Largely based in the lexicons of Latin and Greek, academic vocabulary comprises morphemic structures. Many teachers devote little time to focused instruction in this area because they may lack pertinent morphological and pedagogical knowledge. This article reports findings from a broader three-year longitudinal qualitative case study that explored the experiences of three elementary teachers who engaged in professional development that included study of the morphemic features of academic vocabulary and instructional techniques. This article describes changes teachers made to practice because of their deeper understanding of Latin and Greek morphology and how to teach it. Data sources included in-depth and semistructured interviews, direct observations of classroom practice, and analysis of instructional artifacts. Data analysis revealed that all three participants moved from teacher-centered, definitional approaches towards instruction that was student-centered and focused on developing metalinguistic awareness. Instructional shifts reflected participants’ new understandings about metalinguistic awareness, student-directed problem-solving, and collaborative talk in vocabulary learning. Instructional shifts address metalinguistic awareness, morphology, word consciousness, and Spanish–English cognate instruction—areas that may be overlooked in many classrooms.